2014
DOI: 10.1007/s00276-014-1307-5
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral symmetrical supernumerary heads of biceps brachii with rare pectoralis major insertion

Abstract: During a routine dissection of a 51-year-old Caucasian male cadaver, bilateral symmetrical supernumerary heads (SH) of the biceps brachii muscles with insertion into the pectoralis major (PM) muscles were discovered. Multiple case reports have documented supernumerary heads for the biceps brachii; however, none have shown bilateral insertion into the pectoralis major. This study describes a previously undocumented variation of the SH that has potential for clinical impact. Healthcare providers could be confoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Even though the embryological explanation of the accessory heads of BB was well described, the supernumerary head originating from the pectoralis major described herein has rarely been described to the best of our knowledge. The supernumerary head in this cadaver is likely the result of some minor failure of some of the complex regulation system that acts in concert to ensure proper placement of myogenic cell groups during limb development, as previously suggested (Fraser et al 2014). Taken together, such dysgenesis including the division of origin and the anomalous insertion into the pectoralis major could explain the development of this case.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Even though the embryological explanation of the accessory heads of BB was well described, the supernumerary head originating from the pectoralis major described herein has rarely been described to the best of our knowledge. The supernumerary head in this cadaver is likely the result of some minor failure of some of the complex regulation system that acts in concert to ensure proper placement of myogenic cell groups during limb development, as previously suggested (Fraser et al 2014). Taken together, such dysgenesis including the division of origin and the anomalous insertion into the pectoralis major could explain the development of this case.…”
Section: Discussionmentioning
confidence: 59%
“…Macalister (1875) reported the 48 variations of BB, among which only 2 cases were related to the pectoralis major: a slip to the short head from the tendon insertion of pectoralis major and an instance of the origin of the long tendon of the BB from the tendon of pectoralis major. This variant has recently been reported in two cases, unilaterally (Sargon et al 1996) or bilaterally (Fraser et al 2014). Previous works showed the presence of a supernumerary head originated from the pectoralis major, but we report herein three supernumerary heads associated with a rare origin from the pectoralis major muscle with the other two supernumerary heads documented with the most common form originating from the humerus.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Bilateral SH of BB having origin from the pectoralis major muscle, as reported earlier, is also seen in the present study. 10 These extra/supernumerary fibers of biceps originating from pectoralis major tendon are prone to rupture or tear in young healthy athletes undergoing strenuous exercises.…”
Section: Discussionmentioning
confidence: 99%
“…According to Emeka and Emmanual (2009), unilateral occurrence of third head of biceps brachii muscle together with its abnormal origin of short head from the acromion and from the supraglenoid tubercle. Recent findings from Fraser et al (2015) also observe the clinical importance of supernumerary head of biceps brachii inserted at pectoralis major muscle. While Kopuz and co-workers (1999) observed that the third head of BB commonly begin from the anterior surface of the humerus distal to the insertion of the coracobrachialis muscle.…”
Section: Discussionmentioning
confidence: 99%